2015
DOI: 10.14434/pders.v34i2.19224
|View full text |Cite
|
Sign up to set email alerts
|

College Students with Physical Disabilities: Common On Campus, Uncommon in the Literature

Abstract: College students with physical disabilities were among the first students to receive disability supports in higher education in the United States, and the earliest journal articles in disability services focused almost exclusively on this cohort. As more students with a range of disability types have accessed higher education over the past 25 years, the body of professional literature has developed correspondingly. However, research related to students with physical disabilities is relatively sparse. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
3
13
0
6
Order By: Relevance
“…The results obtained coincide with the studies developed by Rodríguez-Martínez and Álvarez-Arregui [11], Sosa [13], Castellana and Sala [30], and Álvarez-Pérez and López-Aguilar [24], who concluded that university teachers need more preparation to be able to work with disabled students [31]. Nevertheless, teachers had a positive perception regarding the inclusion of students with disabilities in university classrooms [32][33][34]. However, university teachers do not train or attend training activities related to special needs.…”
Section: Discussionsupporting
confidence: 87%
“…The results obtained coincide with the studies developed by Rodríguez-Martínez and Álvarez-Arregui [11], Sosa [13], Castellana and Sala [30], and Álvarez-Pérez and López-Aguilar [24], who concluded that university teachers need more preparation to be able to work with disabled students [31]. Nevertheless, teachers had a positive perception regarding the inclusion of students with disabilities in university classrooms [32][33][34]. However, university teachers do not train or attend training activities related to special needs.…”
Section: Discussionsupporting
confidence: 87%
“…Respecto a los contenidos en la formación, el profesorado considera que es importante conocer sus obligaciones legales, técnicas en el diseño del currículo, ajustes en la enseñanza, información sobre recursos disponibles para estudiantes con discapacidad, uso efectivo de prácticas instruccionales, conocimientos de las características de la discapacidad o información sobre cómo acceder a los servicios de los estudiantes (Cook & cols., 2009;Gelbar, Madaus, Lombardi, Faggella-Luby, & Dukes, 2015).…”
Section: Introductionunclassified
“…This time it was my hand. (Joe, 26-01-2017) Like the cited incidences above, Gelbar, Madaus, Lombardi, Faggella-Luby and Dukes (2015) reported experiences where students with disabilities faced challenges such as inaccessible buildings, rigid curricula and negative attitudes of staff and lecturers. Similarly, Banda-Chalwe, Nitz and De Jonge (2013) contended that accessibility to premises, facilities and services was a right of people with disabilities.…”
Section: Inaccessible Learning Environment (Spatiality)mentioning
confidence: 99%